EDUCATION IN SEARCH OF THE ADEQUACY PRINCIPLE - Y. V. Larin (Образование и наука)
The paper discusses the acute methodology problem: elicitation of the fundamental principle of modern education. In the course of retrospective analysis, the author attempts to trace the essence and comparative historical specificity of the principle in question, and find out whether the currently declared one actually corresponds with the society demands and time requirements.Consequently, the author singles out three successive historical types of education, each of them based on the respective ideological and methodological assumptions. The first one (the 17th – mid-19th century), based on the ontological system of the «Man and Nature», regards the man as a natural creature and proclaims a fundamental educational principle of adequacy to nature. The second type, formed by the end of the 19th century and based on the ontological system of the «Man and Society», takes the man as a social creature and puts forward a fundamental educational principle of adequacy to society. And finally, the multi-dimensional ontological system of the «ManNature-Culture-Society», developed in the mid-20th century, defines the man as a bio-socio-cultural creature and forms a basis for a new fundamental educational principle of adequacy to culture.The paper maintains that the principle of adequacy to nature corresponds with the classical period of education history; orientation on the social adequacy represents its non-classical stage; and consequently, the principle of cultural adequacy signifies the post-non-classical phase. In conclusion, the author argues that resumption of the initial educational principle of adequacy to nature can be regarded as moving backward.